Psychological Effects of Blended Learning to the Faculty of Sultan Kudarat State University, Philippines - John Christian Manghano; Edlyn Joy Magbanua; Adonis Besa (Universitas Pendidikan Indonesia (UPI), 2022)
The study on the Psychological Effects of Blended Learning among the Faculty of Sultan Kudarat State University was conducted to determine the blended learning and its psychological effects on the teachers. The result shows that modular learning is satisfactorily implemented while online learning is moderately implemented. When it comes to the psychological effects of blended learning in terms of teachers’ anxiety, the teachers are moderately experiencing it and in terms of teachers’ distress and boredom, the teachers are seldom experiencing it. The top 5 issues and concerns on blended learning are also asked.